2023
DOI: 10.3389/fmed.2023.1258661
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of immunosuppressive agents during hemoperfusion in a sheep model

Bettina Leber,
Uwe Liebchen,
Lisa Rohrhofer
et al.

Abstract: IntroductionHemoadsorption shows promising signals in organ preservation and post lung transplantation. However, its potential impact on the pharmacokinetics of immunosuppressant drugs (ID) is still unknown.MethodsIn this interventional study, CytoSorb® hemoperfusion was tested in healthy sheep (n = 5) against a sham extracorporeal circuit (n = 3). Seven different ID (tacrolimus (TAC), cyclosporin A (CYA), mycophenolate mofetil (MMF), everolimus (EVER), basiliximab (BAS), methylprednisolone (MP) and prednisolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“… 35 Also, a very recently published large animal study reported on an adsorption rate of less than 5% for immunosuppressive agents such as tacrolimus, cyclosporin A, mycophenolate mofetil, everolimus, and methylprednisolone during 6 h of in vivo extracorporeal haemoadsorption treatment. 36 Data presented in our RCT strongly substantiate these previous investigations. Similar MPA concentrations were measured pre‐CPB and at 2 h of CPB run in the study groups ( Figure 4 ), and there were no differences in the frequencies of cardiac allograft rejection over the 1‐month follow‐up period between the groups ( Table 3 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 35 Also, a very recently published large animal study reported on an adsorption rate of less than 5% for immunosuppressive agents such as tacrolimus, cyclosporin A, mycophenolate mofetil, everolimus, and methylprednisolone during 6 h of in vivo extracorporeal haemoadsorption treatment. 36 Data presented in our RCT strongly substantiate these previous investigations. Similar MPA concentrations were measured pre‐CPB and at 2 h of CPB run in the study groups ( Figure 4 ), and there were no differences in the frequencies of cardiac allograft rejection over the 1‐month follow‐up period between the groups ( Table 3 ).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Lindstedt et al did not find histopathological signs of acute rejection at 1‐ and 3‐month post‐transplant in patients who received cytokine adsorption during lung transplantation, compared to patients managed without the adsorber 35 . Also, a very recently published large animal study reported on an adsorption rate of less than 5% for immunosuppressive agents such as tacrolimus, cyclosporin A, mycophenolate mofetil, everolimus, and methylprednisolone during 6 h of in vivo extracorporeal haemoadsorption treatment 36 . Data presented in our RCT strongly substantiate these previous investigations.…”
Section: Discussionsupporting
confidence: 88%
“…These bene ts translate to lower 30-day mortality in intraoperative hemoadsorption patients treated signi cantly. Notably, no device-related adverse events were reported (Evidence table, Additional le 2), suggesting that there was also no clinically relevant inadvertent immunosuppressant removal, consistent with the recently published animal study showing minimal removal of these agents by CytoSorb [27].…”
Section: Heart Transplantationsupporting
confidence: 81%
“…The use of hemoadsorption in organ transplants has been controversial due to the already discussed potential for unwanted drug removal, specifically immunosuppressants. However, a detailed investigation in a large animal model reassuringly reported a minimal level of removal with frequently used immunosuppressant regimens [ 63 ]. A very recent RCT [ 64 ] confirmed CytoSorb ® did not affect levels of mycophenolic acid, used to prevent organ transplant rejection, and found that concentrations were comparable to the control group at all pre-defined time points.…”
Section: Discussionmentioning
confidence: 99%